Optimization of Hot Water Treatment in Red Dragon Fruit Using Response Surface Methodology - Yuniarsih Yuniarsih; Emmy Darmawati; Siti Mariana Widayanti (Institut Pertanian Bogor, 2026)
Red-fleshed dragon fruit is recognized as a superfruit because of its betacyanin content, a natural pigment with antioxidant properties. However, the fruit is highly perishable after harvest, requiring effective postharvest handling, such as Hot Water Treatment (HWT). This study aimed to determine the optimum combination of temperature, immersion time, and maturity index using Response Surface Methodology (RSM) with a Box-Behnken Design. The optimized quality parameters included lightness value (L*), total soluble solids (TSS), betacyanin content, and vitamin C content. The optimum conditions were found to be 50°C for 15 min at maturity index IV, achieving a desirability of 0.885. The predicted model values were 28.40 (L*), 13.5 °Brix (TSS), 56.44 mg/L (betacyanin), and 3.53 mg/100 g (vitamin C). Validation of the optimal treatment revealed that only the quality attributes of total soluble solids (13.1 °Brix) and vitamin C (3.36 mg/100 g) were in close agreement with the predicted model values. In contrast, the model demonstrated lower predictive accuracy for lightness (L*) and betacyanin content. Keywords: Box-Behnken Design, dragon fruit, hot water treatment, response surface methodology